2021
DOI: 10.1080/0267257x.2021.1966077
|View full text |Cite
|
Sign up to set email alerts
|

Constructing the food waste issue on social media: a discursive social marketing approach

Abstract: The purpose of the paper is to examine how market actors participate in the socio-cultural construction of the food waste issue through social media. The paper draws from practice theory and adopts a research approach combining netnography and discourse analysis. The data consist of postings within a vivid social media discussion during a social marketing campaign. The findings shed light on how different market actors construct the food waste issue through discourses of explanation, exhibition and appeal. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 103 publications
(177 reference statements)
0
11
0
Order By: Relevance
“…Finally, digital technologies can enable innovative marketing strategies on social media. Sutinen and Närvänen (2021) pointed out that social media can construct the food waste issue socially by leveraging discourses for fueling and facilitating practice changes. Based on this premise, they explored what kinds of market actors participate in the discussion of the food waste issue on social media, what kinds of food waste issue discourses can be identified and what kinds of potential the different discourses have to change practices in the context of food waste.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, digital technologies can enable innovative marketing strategies on social media. Sutinen and Närvänen (2021) pointed out that social media can construct the food waste issue socially by leveraging discourses for fueling and facilitating practice changes. Based on this premise, they explored what kinds of market actors participate in the discussion of the food waste issue on social media, what kinds of food waste issue discourses can be identified and what kinds of potential the different discourses have to change practices in the context of food waste.…”
Section: Resultsmentioning
confidence: 99%
“…The transition to a circular economy also depends on the processes of socio-cultural construction of specific circular-economy-related issues. In this regard, Sutinen and Närvänen (2021) investigated how market actors participate in the socio-cultural construction of the food waste issue through social media. The findings shed light on how different market actors engage in discourses of explanation, exhibition and appeal to construct the food waste issue socially.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the role of social innovation in food redistribution activities, we identified several future research directions, as shown in Supplementary Table S2. First, existing studies (Huang and Tsai, 2021;Lombardi and Costantino, 2020;Sutinen and Narvanen, 2021) realized that the key to maximizing the performance of food redistribution activities is to build connections between the 'wasted places' and the 'needed places' through deploying different social innovation measures, such as online markets and online food-sharing communities. However, the performance of the measures adopted to tackle the connectivity gaps appears to have been largely ignored by the extant literature (De los Mozos et al, 2020).…”
Section: Food Redistribution Rescue Donation and Sharing-related Reco...mentioning
confidence: 99%
“…Message framing has to be appropriate for the intended audience for any campaign to be successful (Pearson and Perera, 2018) and for today's tech-savvy audience, the nudging messages should be relayed quickly, effectively and widely (Soma et al, 2020) through digital platforms (Mullick et al, 2021). Social media can help highlight the issue of food waste (Sutinen and Närvänen, 2022;Jenkins et al, 2022), and posting about the issue can act as a form of nudge to encourage food waste prevention (Teoh et al, 2022). However, to date, the effectiveness of digital nudges on food waste habits is still not clear (Farr-Wharton et al, 2020;Lazell, 2016); therefore, its application was examined in this study among restaurant patrons with the following hypotheses (H1):…”
Section: Nudge Theory and Digital Nudgingmentioning
confidence: 99%